Apoptosis Effects of Oxalis Corniculata L. Extract on Human MCF-7 Breast Cancer Cell Line: - Hamidi, Masoud; Gholipour, Amir Reza; Jafari, Leila; Ramezanpour, Mahsa; Evazalipour, Mehdi; Chavoshi, Maral; Yousefbeyk, Fatemeh; Jani Kargar Moghaddam, Saghi; Yekta Kooshali, Mohammad Hossein; Ramezanpour, Nahid; et al. (Galen Medical Journal, 2022)
Background: Recently, the non-toxic properties of natural plant products have gained more focus as anticancer agents. Therefore, this study aimed to assess the apoptosis effects of the ethanolic extract of Oxalis corniculata on the MCF-7 breast cancer cell line. Materials and Methods: In this experimental study, aerial parts of O. corniculata were collected in Lahijan city (Iran), and after confirmation, they were dried and extracted with ethanol for 24 h. Then, the total phenolic and flavonoid contents of the extract were measured. The 2,2-diphenyl-1-picrylhydrazyl radical scavenging assay was used to measure the antioxidant properties of the extract. Selected cell lines (MCF-7 and human dermal fibroblast) were cultured in 6-wells dishes (1Ã—106 cells/well). After 72 h of treating the extract, cytotoxicity was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The expression of apoptotic genes (such as p53, bcl-2, bax, and CD95) was studied by real-time polymerase chain reaction (PCR). Results: The extract’s total phenolic content was 31.30Â±02 Âµg of gallic acid equivalents/mg of dry extract, and the total flavonoid content was 49.61Â±04 Âµg of quercetin as equivalents/mg of extract. The antioxidant activity of O. corniculata was measured at the dose of 619.2 Âµg/Âµl, indicating that it decreases cancer cell viability and enhances apoptosis. Within the half maximal inhibitory concentrations, real-time PCR revealed substantial increases in p53 (P<0.001), CD95 (P<0.05), and bcl-2 expression (P<0.05) in MCF-7 cells treated with O. corniculata. Conclusion: This study suggests that O. corniculata may cause apoptosis by oxidative stress in cancer cells